Competency-driven benefits realization model for minimization of post-contract transaction costs in design-build (d&b) delivery systems - Raji, Abdulazeez Umar (2017)
The construction industry has been struggling with the issue of inconsistent performance with respect to cost of projects, completion time and the delivery of a quality product. In an attempt to address this issue the Design-Build (D&B) project delivery system was initiated primarily to overcome the shortcomings of the traditional procurement strategies. Although, traditionally D&B delivery system was aimed to greatly enhance client‘s benefits, this has not significantly been achieved. It lacks clear benefits realization management process to deliver the planned client‘s benefits. In particular, the Transaction Costs (TCs) incurred at the post-contract phase (PTCs) through D&B system has been the subject of criticism, wherein it has been unable to achieve the expected resounding success of a total shift away from the issues attributed to the traditional systems. This research aims to establish the importance of leveraging on D&B project team-competency and commitment structured within a strategic Benefits Realization Management framework to optimize client‘s benefits in terms of minimizing PTCs. The focus is on the aspect of competencies of key project participants and their project team commitment with respect to minimizing TCs that is structured within a Benefits Realization Management (BRM) practice. Questionnaire survey data was obtained from 231 respondents out of 357 administered questionnaires to G7 contractors registered under CIDB Malaysia that was based on a systematic sampling of the existing CIDB contractor database. The partial least squares structural equation modeling (PLS-SEM) technique was used to test the relationships being hypothesized and to validate and confirm the developed Competency Driven Benefits Realization Model (CD-BREM). Exploratory preliminary research findings reveal that post-contract TCs for D&B projects range from 3.5% to 13.5% of the project value. The primary research findings reveal that D&B team commitment has partial mediating effect between team competency and post-contract TCs. Whilst, BRM was found to have a partial mediating effect between team competency and post-contract TCs and no moderating effect as initially hypothesized. In general the research findings indicate that team competency, commitment and BRM have significant positive influences on post-contract TCs. This research provides a multi-dimensional perspective of the D&B project benefits realization concept and has the potential to address the issue of minimizing PTCs, which is seen as a social waste of wealth. Using CD-BREM it is possible to identify key human factors that can contribute to high project performance that also serves as an enabling mechanism for realizing the full potential of the D&B method for delivering successful projects. This research is timely to help reverse the trend of poor performance within the construction industry as a whole. Further work on the implementation of this CD-BREM model on construction projects and the consideration of including additional independent variables in the research theoretical framework can be explored to strengthen the credibility of the outcome of this research which is aimed at minimizing PTCs.